25 Vascular access site and outcomes among 26, 807 CTO-PCI cases from the national angioplasty audit. (27th November 2017) - Kinnaird, Tim; Anderson, Richard; Gallagher, Sean; Large, Adrian; Strange, Julian; Ludman, Peter; Belder, Mark de; Nolan, James; Hildick-Smith, David; Mamas, Mamas
Abstract : Background: Use of radial access in chronic total occlusion percutaneous coronary intervention (CTO-PCI) warrants further investigation. Using the BCIS PCI database, access site choice and outcomes after CTO-PCI were assessed. Methods: Data were analysed on 26 807 elective CTO-PCI procedures performed between 2006 and 2013. Multivariate logistic regression was used to identify predictors of access site choice and its association with outcomes. Results: There was a decrease in femoral artery (FA) utilisation from 84.6% in 2006 to 57.9% in 2013. Procedural factors associated with FA access included dual access (OR 4.01, 3.63–4.44), Crossboss/Stingray (2.06, 1.55–2.75), IVUS (1.26, 1.12–1.40), and micro-catheter use (1.15, 1.06–1.25). There was an association between FA access and the number of CTO devices used (p=0.001 for trend). An access site complication (1.5 vs 0.5%, p<0.001), major bleeding (0.8 vs 0.2%, p=0.007), transfusion (0.4 vs 0%, p<0.001) and 30 day death (0.7 vs 0.1%, p=0.002) were more frequent in patients undergoing CTO-PCI using FA access. An access site complication during CTO-PCI was associated with significant increases in transfusion (8.0 vs 0.1%, p<0.001), procedural coronary complication (17.3 vs 5.8%, p<0.001), major bleeding (8.4 vs 0.3%, p<0.001) and mortality at all time points. Conclusions: FA access remains predominant during CTO-PCI with case complexity and device size associated with its use. Access site complications were more frequent with FA use and strongly correlated with adverse outcomes.